The Association between Molar-Incisor Hypomineralization and Dental Caries with Socioeconomic Status as an Explanatory Variable in a Group of Finnish Children - Wuollet, Emma (Int J Environ Res Public Health, 2018)
The aim of this study was to investigate if a developmental enamel defect known as Molar-Incisor Hypomineralization (MIH) is associated with dental caries. Socioeconomic status (SES) was examined as a confounding factor between caries and MIH. In this cross-sectional study, 636 children, aged 8 to 13 years, from three towns (two rural areas and one urban area) in Finland were examined for MIH in line with the criteria of the European Academy of Paediatric Dentistry. Caries status for permanent teeth was recorded as decayed, missing and filled teeth (DMFT). Caries experience (DMFT > 0) in the first permanent molars (FPMs) was set as an outcome. SES was determined using a questionnaire completed by parents. The prevalence of MIH was 18.1%. The mean DMFT in FPMs for children with MIH was higher than for their peers, 1.03 ± 1.25 vs. 0.32 ± 0.80 (p = 0.000, Mann-Whitney U test). In a multivariate analysis using the generalized linear mixed model where locality, SES, age and MIH were taken into account as caries risk indicators, MIH was the strongest risk indicator of caries in FPMs (Odds Ratio: 6.60, 95% Confidence Interval: 3.83–11.39, p = 0.000). According to the study results, children with MIH have a higher risk for dental caries than children without MIH.